(untitled) (Colombia Medica, 1988)
The present work analyses the seroprevalence of antibodies for HTLV-I in populations of the Pacific coast (less than 500 meters altitude) and inland populations at the Cauca River Valley (greater than 800 meters altitude) in the southwestern region of Colombia. There is a statistically significant increase in seropositivity in older persons (> 40 years). The geographical features of these populations, separated by a mountain range and at different altitudes, constitute a crucial epidemiologic model for future studies.